The Role of Artificial Intelligence Technologies in Providing Legal Consultations - Muna Naeem Jaaz (Journal of Legal Sciences, 2024)
Artificial intelligence is a technology that has a superior ability to learn, develop, and the ability to make appropriate decisions. It has the ability to deal with situations and develop appropriate solutions to them, and the ability to sweep the field of providing legal services such as consultations that were traditionally provided through a lawyer or a legal consulting office. Today, because of these technologies, legal advice is provided by default by a smart legal consultant. We have adopted a comparative analytical approach by defining the concept of this technology, indicating the position of legislation, as well as reviewing judicial developments in order to assess the final position of the smart legal consulting system. One of the results of the study of smart legal advice is the difficulty of providing it without human intervention because the first is a mental product, so the traditional legal adviser is indispensable, especially in thorny legal matters that need explanation and explanation. As for liability within the scope of artificial intelligence technologies, everyone agrees on the existence of liability and compensation, but the dispute revolves around the basis of that liability and the extent to which those technologies have the legal personality to claim responsibility